10 Rules for Constructive Conflict - Victor William Harris (EDIS)
Determining how we handle conflicts, whether constructively or destructively, is a good way to see how functional or dysfunctional we are acting in our relationships. Take a minute and complete this quiz to see if you handle conflict in a constructive or destructive way. It will help you realize what you are already doing well and what skills you might still want to work on a little more. This 3-page fact sheet was written by Victor William Harris and published by the UF Department of Family, Youth and Community Sciences, January 2012.